Collective bargaining in seven European countries throughout the pandemic - Oscar Molina; Roberto Pedersini (International Labour Organization (ILO), 2022)
This Working Paper investigates developments in social dialogue and collective bargaining during the first two years of the COVID-19 pandemic in a selection of European countries. The paper provides an overview of government and social partner responses. In describing responses, the main goal of this paper is to identify the dimensions that can help explain the variety of responses, but also their commonalities. The paper also aims at understanding the factors that may have promoted the activation of social dialogue over economic and social policies and broaden the role of collective bargaining and industrial relations, as opposed to unilateral interventions designed by national governments. The paper lays out an analytical framework based on the COVID impact in each country, national industrial relations institutions and the nature of the government in office. In this general framework, we observe how national industrial relations institutions play a key role in explaining the responses in terms of the level and quality of social dialogue and the role of collective bargaining. Particularly important has been the role of strong sectoral collective bargaining institutions, allowing sectoral actors to negotiate specific responses considering the impact and the needs of the sector.
Keywords: 330; collective bargaining; COVID-19